Solid-State lithium-ion battery electrolytes: Revolutionizing energy density and safety - P.U. Nzereogu; A. Oyesanya; S.N. Ogba; S.O. Ayanwunmi; M.S. Sobajo; V.C. Chimsunum; V.O. Ayanwunmi; M.O. Amoo; O.T. Adefemi; C.C. Chukwudi (Hybrid Advances)
Solid-state lithium-ion batteries (SSLIBs) are poised to revolutionize energy storage, offering substantial improvements in energy density, safety, and environmental sustainability. This review provides an in-depth examination of solid-state electrolytes (SSEs), a critical component enabling SSLIBs to surpass the limitations of traditional lithium-ion batteries (LIBs) with liquid electrolytes. Conventional LIBs face significant challenges such as thermal instability, flammability, leakage, limited electrochemical windows, and environmental concerns. SSLIBs, however, eliminate these risks by utilizing solid electrolytes, which exhibit higher ionic conductivities, increased electrochemical stability, and reduced safety hazards. This review explores a variety of solid electrolytes, including oxide, sulfide, perovskite, anti-perovskite, NASICON, and LISICON-based materials, each with unique structural and electrochemical properties that enhance lithium-ion mobility and battery performance. Additionally, advancements in interfacial engineering, cathode and anode material optimization, and manufacturing techniques are discussed. The potential of SSLIBs in transforming applications across industries—from electric vehicles to large-scale energy storage systems—is underscored, highlighting the path toward more efficient, safer, and sustainable battery technologies.